Long‐term changes in the impacts of global warming on leaf phenology of four temperate tree species - Chen, Lei; Huang, Jian‐Guo; Ma, Qianqian; Hänninen, Heikki; Tremblay, Francine; Bergeron, Yves (Global change biology, 2019)
Contrary to the generally advanced spring leaf unfolding under global warming, the effects of the climate warming on autumn leaf senescence are highly variable with advanced, delayed, and unchanged patterns being all reported. Using one million records of leaf phenology from four dominant temperate species in Europe, we investigated the temperature sensitivities of spring leaf unfolding and autumn leaf senescence (ST, advanced or delayed days per degree Celsius). The ST of spring phenology in all of the four examined species showed an increase and decrease during 1951–1980 and 1981–2013, respectively. The decrease in the ST during 1981–2013 appears to be caused by reduced accumulation of chilling units. As with spring phenology, the ST of leaf senescence of early successional and exotic species started to decline since 1980. In contrast, for late successional species, the ST of autumn senescence showed an increase for the entire study period from 1951 to 2013. Moreover, the impacts of rising temperature associated with global warming on spring leaf unfolding were stronger than those on autumn leaf senescence. The timing of leaf senescence was positively correlated with the timing of leaf unfolding during 1951–1980. However, as climate warming continued, the differences in the responses between spring and autumn phenology gradually increased, so that the correlation was no more significant during 1981–2013. Our results further suggest that since 2000, due to the decreased temperature sensitivity of leaf unfolding the length of the growing season has not increased any more. These finding needs to be addressed in vegetation models used for assessing the effects of climate change. Here, we found both impacts of climate warming on both spring and autumn phenology declined in recent decades. In addition, the impacts of rising temperature associated with global warming on spring leaf unfolding were stronger than those on autumn leaf senescence. The timing of leaf senescence was positively correlated with the timing of leaf unfolding during 1951–1980. However, as climate warming continued, the differences in the responses between spring and autumn phenology gradually increased, the correlation was no more significant during 1981–2013. These findings need to be addressed in vegetation models used for assessing the effects of climate change.